ERP Enhancement to Accommodate Business Process in Furnishing Company - Firmansyah, Deny (Swiss German University, 2015)
Avoiding customization to enhance of an ERP implementation consider as one of successful keyfactor. Within this paper, the writer tries to answer the question of â€œThe expectation of ERP able tofit in with company business flow in a standard way and why enhancing the system is almost notavoidableâ€.To answer this question, the writer will use a case study of a furnishing distribution company or thesupplier to retail store in the process of integration of ERP system with logistic process.